Science interdisciplinary learning approach: a study interdisciplinary thinking skills and literacy environment - Santiani, Santiani; Reffiane, Fine; Winarto, Winarto (Intelektual Pustaka Media Utama, 2024)
The formation of environmental literacy in the education system through education for sustainable development (EfSD) experiences many obstacles. The aim of the research is to analyze the impact of interdisciplinary science learning for interdisciplinary oriented education for sustainable development to improve interdisciplinary thinking and environmental literacy of prospective teachers. The experimental method with a quasi-experimental pretest posttest group design was used in this study. The data collection technique used is an environmental literacy questionnaire and an interdisciplinary thinking test. Data analysis technique used independent t test. The results obtained were that the science interdisciplinary learning effective in improving interdisciplinary thinking performance and environmental literacy. The performance of students’ interdisciplinary thinking affects environmental literacy of students. The university forms student teacher candidates who have the ability to think interdisciplinary so that they can manage science learning in an interdisciplinary and environmentally literate manner. The implication of this research is the importance of fostering interdisciplinary thinking and environmental literacy at all levels of education.